Preliminary analysis for a sustainable urban design in the El Palaciero community of Lara State (Gaceta Técnica, 2024)
The purpose of this research is to carry out a preliminary analysis of the urban and social context of the El Palaciero sector, which allows establishing a diagnosis in order to propose a sustainable urban design proposal adapted to the existing industrial and agroindustrial influence. A survey was carried out among the residents of the study area to know their needs and perceptions, in addition to a physical - social - environmental diagnosis of the area under study through the direct observation technique and an exhaustive bibliographic review. The information collected allowed us to determine that El Palaciero has great potential due to its centrality, with respect to the adjacent sectors and being within the direct urban environment of the Lara Special Economic Zone of the Palavecino
Keywords: urban development; urban planning; sustainable design; El Palaciero